Development of the Learning System of Flipped-Guided Inquiry-Based Learning (FGIL) Using Moodle on Chemical Equilibrium material - Fitriana Rahmah Siregar; Mawardi Mawardi (Indonesian Journal of Educational Studies, 2022)
Abstract. The Covid-19 pandemic in Indonesia has impacted the education sector, requiring learning activities to be shifted online. So that it becomes a new challenge for teachers and students to be able to carry out learning according to this situation and with the demands of the digitalization revolution 4.0. This study aimed to develop and determine the validity and practicality the Learning System of Flipped-Guided Inquiry-Based Learning (FGIL)  using Moodle on chemical equilibrium material. This research is a Research and Development (R&D) with a Plomp development model. The subjects of this research are students of class XI SMAN 8 Padang, chemistry teachers, and lecturers in the chemistry department of FMIPA UNP. The research instruments used were validity sheets for validity testing and teacher and student response questionnaires for practicality tests. The average value obtained from 5 validators is 0.90 with a valid category. The average value obtained from the practicality test is 85%, with a very practical category. The results of the validity and practicality show that the learning system of Flipped-Guided Inquiry-Based Learning (FGIL) using Moodle on chemical equilibrium material developed is valid and practical.